Analysis of the combustion mechanism of diesel surrogate fuel under CO2/O2 atmosphere. (1st February 2022) - Liu, Yongfeng; Wang, Long; Bi, Guijun; Wei, Ping; He, Xu; Yao, Shengzhuo; Song, Jinou; Sun, Hua
Abstract: Closed-cycle diesel engine (CCDE) can effectively control CO2 emissions and reduce the greenhouse gas effect, but diesel fuel combustion under an atmosphere with CO2 has the problem of misfire and unclear mechanism. In order to study the CO2 impact on diesel combustion under the CO2 /O2 atmosphere, a quantum chemical (QC) model of diesel surrogate fuel (DSF) is proposed, which takes into account the CO2 pyrolysis effect ( C O 2 ⇆ C O + 1 2 O 2 ) and the new reaction of OH radical generation from pyrolysis products ( C O + O 2 + H ∙ → C O 2 + O H ∙ ). Firstly, the active sites of the DSF molecules are predicted by average local ionization energy (ALIE) and electrostatic potential (ESP). New chemical reaction paths are obtained using ab initio theory and density functional theory combined with thermodynamic combination algorithm. The QC model is then established by sensitivity analysis and simplification of the mechanism and computational fluid dynamics (CFD) simulation of constant volume combustion chamber (CVCC.) Secondly, the CVCC experiment bench and visualization system are set up. The flame propagation at different times (1.5 ms, 1.9 ms, 2.3 ms, 2.7 ms, 3.1 ms and 3.5 ms) are captured by high-speed cameras under four different CO2 concentrations (air condition, 50%CO2  + 50%O2, 43%CO2  + 57%O2 and 35%CO2  + 65%O2 ). Finally, the comparison between experiment and model shows that the QC model is suitable for studying combustion characteristics of diesel fuel under CO2 /O2 atmosphere. Under maximum CO2 concentration (50%CO2  + 50%O2 ), The maximum errors of flame combustion limit length (FCLL) and Flame longitudinal section area (FLSA) are 8.54% and 4.94%, respectively. In addition, the CO2 pyrolysis reaction and the new reaction of generating OH radicals indicate that the CO2 chemical effect can promote the combustion of diesel fuel under CO2 /O2 atmosphere.